Microparticle-associated tissue factor activity and venous thrombosis in multiple myeloma - Auwerda, Johannes J. A.; Yuana, Yuana; Osanto, Susanne; de Maat, Moniek P. M.; Sonneveld, Pieter; Bertina, Rogier M.; Leebeek, Frank W. G. (Thrombosis and Haemostasis, 2011)
Multiple myeloma (MM) is associated with an increased risk of venous thromboembolic (VTE) complications. Aim of this study was to measure microparticle-associated tissue factor (MP-TF) activity in patients with newly diagnosed MM before and after chemotherapy and to investigate whether MP-TF activity is associated with VTE. MP-TF activity was assessed in 122 newly diagnosed MM patients who were eligible for combination chemotherapy. MP-TF activity levels (17.6 fM Xa/min [8.6–33.2] (median [IQR]) were higher in untreated MM patients compared to normal healthy volunteers (4.1 fM Xa/min [2.3–6.6], p <0.001). MP-TF activity prior to the start of treatment was not different between patients who developed a VTE during follow-up (n=15) and those who did not (n=107). In 75 patients in whom plasma was obtained before and after chemotherapy, MP-TF activity decreased significantly (from 17.4 [10.2–32.8] to 12.0 [7.0–18.5] fM Xa/min, P=0.006). MP-TF activity remained, however, elevated in patients who developed VTE (15.1 [10.3–25.2]), in contrast to patients not developing VTE (11.4 [7.0–25.2], P<0.001). In conclusion, MP-TF activity is increased in patients with MM. Whether MP-TF activity has a pathogenetic role in VTE in MM patients remains to be established in future studies.
Keywords: Multiple myeloma; tissue factor; microparticles; venous thrombosis